USING MOODLE EDUCATIONAL ENVIRONMENT FOR LINEAR ALGEBRA TESTING DURING THE TRAINING OF FUTURE TEACHERS OF MATHEMATICS - Дубовик, Віталій (SWorldJournal, 2023)
The article highlights the relevance of the introduction of information and communication technologies in the educational process, in particular, software tools and online testing systems. The peculiarities of using the Moodle educational environment for